Усовершенствование редукторов производства ГП НПКГ "Зоря"-"Машпроект" - Мироненко, А. И.; Спицын, В. Е.; Гамза, Е. А.; Матвеевский, Д. В.; Дзятко, С. А. (НТУ "ХПИ", 2015)
Представлены новые направления в проектировании, изготовлении и испытании зубчатых передач производства ГП НПКГ "Зоря"-"Машпроект". Приведены конструктивные особенности зубчатых зацеплений и других элементов редукторов. Показана модернизация редукторного производства высокоточным оборудованием и современными испытательными стендами. Возможности редукторного производства и квалификация его сотрудников дают возможность наладить производство зубчатых передач для любых отраслей промышленности Украины, а также выполнять большие объемы зарубежных заказов.

The article presents the new directions in the design, manufacture and testing of gearing production "Zorya"-"Mashproekt." Constructive features of gears and other elements of gear. In order to reduce weight and size and improve the performance gears and bearings designers created a series of original, multi-threaded cylindrical and bevel gears, schematics which are protected by patents of the USSR and Ukraine. It is shown that the modernization of the production of high-precision equipment gear. For example, the manufacture of cylindrical gears with the help of German machine Gleason-PFAUTER really reached the fourth degree of accuracy. Noting the existence of modern test stands: made conical and cylindrical gears up to 10...12MW are being tested at the stands with closed loop circulating load using hydraulic and mechanical loading devices of its own production. Gear production capabilities and qualifications of its staff allow to establish production of gears for all industries of Ukraine, as well as to carry out large volumes of overseas orders.
SE GTRPC "Zorya"-"Mashproekt" gear boxes improvement
Keywords: зубчатое колесо; зубошлифовальный станок; испытательный стенд; gear box; gear wheels; gear tooth; grinding machines; test benches